2003
DOI: 10.1074/jbc.m302373200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Glycoprotein H of Human Herpesvirus 6 with the Cellular Receptor CD46

Abstract: Human herpesvirus 6 (HHV-6) employs the complement regulator CD46 (membrane cofactor protein) as a receptor for fusion and entry into target cells. Like other known herpesviruses, HHV-6 encodes multiple glycoproteins, several of which have been implicated in the entry process. In this report, we present evidence that glycoprotein H (gH) is the viral component responsible for binding to CD46. Antibodies to CD46 co-immunoprecipitated an ϳ110-kDa protein band specifically associated with HHV-6-infected cells. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…Evidence has been presented in this report that underlines the crucial relevance of the SCR-2 domain of CD46 in HHV-6A binding to HPDA. In contrast, it has been reported that the SCR-2 and SCR-3 domains of CD46 were involved in HHV-6A binding to lymphocytes (18,30). Ongoing experiments are exploring mechanisms of HHV-6B in HPDA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been presented in this report that underlines the crucial relevance of the SCR-2 domain of CD46 in HHV-6A binding to HPDA. In contrast, it has been reported that the SCR-2 and SCR-3 domains of CD46 were involved in HHV-6A binding to lymphocytes (18,30). Ongoing experiments are exploring mechanisms of HHV-6B in HPDA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, soluble gH͞gL was found to bind to both AGS and SVKCR2 cell lines, but not EBV-negative Akata cells, suggesting a specific receptor for gH͞gL (gHgLR) is present on epithelial cells (18). Despite the conservation of gH and gL, the only binding partner of this complex identified thus far is the binding of human herpesvirus (HHV)-6 to CD46 (19), but this does not appear to be functionally significant.…”
mentioning
confidence: 98%
“…At 72 h postinfection, for pulse-chase labeling, the cells were incubated in methionine-free RPMI 1640 for 1 h and then pulse-labeled with Redivue Pro-mix L- 35 S in vitro cell labeling mix (400 Ci/ml; Amersham Pharmacia Biotech) for 30 min. The pulse-labeled cells were chased for 1, 2, and 4 h. At 72 h postinfection, for metabolic labeling, the cells were incubated in methionine-free RPMI 1640 for 1 h and then radiolabeled with Redivue Pro-mix L- 35 S in vitro cell labeling mix (20 Ci/ml) for 16 h. The cells were recovered and lysed in radioimmunoprecipitation (RIPA) buffer (0.01 M Tris-HCl [pH 7.4], 0.15 M NaCl, 1% sodium deoxycholate, 1% Nonidet P-40, 0.1% sodium dodecyl sulfate [SDS], 1 mM EDTA, 1 mM phenylmethylsulfonyl fluoride) for 30 min on ice. After centrifugation at 200,000 ϫ g for 1 h, the supernatants were incubated with MAb AgQ-119-or AgQ-182-protein G-Sepharose (Amersham Pharmacia Biotech) complex at 4°C for 4 h. Immunocomplexes were washed with RIPA buffer to remove unbound proteins.…”
Section: Rt-pcr Reverse Transcription (Rt)-pcr Was Carried Out With mentioning
confidence: 99%
“…Furthermore, the gH-gL-gQ-80K complex of HHV-6A was identified as a viral ligand for human CD46 (27), which is a cellular receptor of . gH has been reported to be the viral component responsible for binding to CD46 (35).In this study, we focused our attention on the analysis of this novel glycoprotein, gQ, which is unique to To further analyze HHV-6 gQ, we performed Northern blotting and found in the gQ gene region another small transcript which encodes a protein of 214 amino acids. MAbs against the predicted protein recognized 37-kDa (gQ-37K) and 34-kDa (gQ-34K) forms in HHV-6A-infected cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation